hubungan peningkatan berat badan dengan penggunaan alat kontrasepsi suntik DMPA di tpmb bidan Imah tahun 2023 - Imah, Imah; Siregar, Rohani (NHM PRESS, 2024)
DMPA contraception is an injectable contraceptive containing only progestin, namely Depo Medroxyprogesterone Acetate (DMPA), which contains 150 mg of DMPA, which is given every three months by intramuscular injection in the area of the gluteus maximus or deltoideus. The design of this study is quantitative research, using Cross Sectional method. The population in this study was 115 respondents with a sample of 89 respondents. The sampling technique uses purposive sampling technique. Research instruments using questionnaires and analysis using univariate analysis and bivariate analysis. The results of the study showed variables related to weight gain, namely Age p value = 0.000 OR value = 91.125, Parity p value = 0.003 OR value = 5.147, Contraceptive Use Period p value = 0.000 OR value = 9.750 and unrelated activity pattern with p value = 0.662. . The conclusion of the researchers is that there is a relationship between age, parity and length of time of contraceptive use with an increase in body weight of DMPA contraceptive users, while for activity patterns there is no relationship with an increase in body weight of DMPA contraceptive users. It is recommended for the public, especially DMPA contraceptive acceptors, to know the side effects of using DMPA contraceptives on weight gain, and for midwives to provide clear counseling to birth control acceptors about contraceptives and their side effects on weight gain